2005
DOI: 10.1111/j.1740-8261.2005.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Determination of Tibial Torsion in the Dog

Abstract: The goal of this study was to develop a method for computed tomographic (CT) measurement of tibial torsion, and to compare this technique with direct anatomic measurement of tibial torsion in cadaveric canine tibiae. Paired hind limbs of 10 cadaveric dogs were mounted on a custom-designed limb holding apparatus. One-millimeter thick, contiguous, transverse CT slices were obtained from the distal femur to the proximal tibia and 2 mm CT slices were obtained from the distal tibia to the proximal tarsus. The tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(118 citation statements)
references
References 8 publications
3
115
0
Order By: Relevance
“…CT scans were used to assess tibial torsion as described previously . Briefly, 0.6 mm thick, contiguous, transverse CT slices were acquired from the proximal and distal 2 cm of all tibiae including at least 4–6 slices of the distal aspect of the femur and proximal aspect of the tarsus.…”
Section: Methodsmentioning
confidence: 99%
“…CT scans were used to assess tibial torsion as described previously . Briefly, 0.6 mm thick, contiguous, transverse CT slices were acquired from the proximal and distal 2 cm of all tibiae including at least 4–6 slices of the distal aspect of the femur and proximal aspect of the tarsus.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic measurement protocols are described for distal femoral varus, known as the anatomic lateral distal femoral angle (aLDFA), angle of anteversion (AA), proximal tibial varus or valgus, which is expressed as the mechanical medial proximal tibial angle (mMPTA)), and tibial torsion . Protocols are also described for measurements using computed tomography (CT) for aLDFA, AA, tibial torsion, and tibial tuberosity displacement (TTD) …”
mentioning
confidence: 99%
“…We adopted the threshold of 10° based on a previous CT study of tibial torsion in normal large breed NCD dogs, which found that the standard deviation of the mean was 5° (Aper et al . ), suggesting that 95% of dogs will be within ±10° of the population mean. The authors are unaware of studies in dogs assessing the clinical significance of tibial rotational malalignment.…”
Section: Discussionmentioning
confidence: 99%